Pelaksanaan kampus mengajar dalam rangka meningkatkan peran mahasiswa Di SDN 95 Kabupaten Kaur, Bengkulu - Ika Pasca Himawati; Umi Habibah (Unri Conference Series: Community Engagement, 2021)
Teaching Campus is a policy set by the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia, which provides opportunities for students to hone students' abilities according to their talents and interests by going directly to the field (elementary school). One of the locations for campus teaching activities is SDN 95 Kaur Regency, Bengkulu. The implementation carried out by these students was also accompanied by Field Supervisors. The performance includes activities: exploring problems that exist in schools, student discussions with school stakeholders, student discussions with field supervisors, implementing programs based on issues that occur in the field, monitoring and evaluating and preparing final reports on student activities. The results of the Campus teaching program activities include: Students strengthen literacy learning, strengthen numeracy, and help to learn during the pandemic, especially at the elementary level. The training lasted for approximately three months. The students' roles in these activities included: Helping teach, Carrying out the technology adaptation process, Assisting in the preparation of school administration and teachers. It is hoped that the presence of students can bring positive changes to teachers, students and schools.